2017
DOI: 10.11606/1807-55092017000nesp089
|View full text |Cite
|
Sign up to set email alerts
|

40 anos da Pós-graduação da EEFE-USP: sua contribuição para a formação de recursos humanos para a docência no ensino superior

Abstract: Rev Bras Educ Fís Esporte, (São Paulo). 2017 Ago; 31(N esp):89-96.• 89 40 anos da Pós-graduação da EEFE-USP: sua contribuição para a formação de recursos humanos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The insertion in the public IHE showed a greater amount of links before the doctorate conclusion, in the same year of the course termination and after the doctorate conclusion. The postgraduate scenario in physical education showed that continuing education in postdoctoral stages has been a demand for a reduced number of graduates, as evidenced in other programs in Brazil 15 . However, most of them engage in teaching career before they finish the course, which may facilitate their subsequent insertion in the job market due the opportunities presented to the students during the course period 12 .…”
Section: Discutionmentioning
confidence: 96%
See 4 more Smart Citations
“…The insertion in the public IHE showed a greater amount of links before the doctorate conclusion, in the same year of the course termination and after the doctorate conclusion. The postgraduate scenario in physical education showed that continuing education in postdoctoral stages has been a demand for a reduced number of graduates, as evidenced in other programs in Brazil 15 . However, most of them engage in teaching career before they finish the course, which may facilitate their subsequent insertion in the job market due the opportunities presented to the students during the course period 12 .…”
Section: Discutionmentioning
confidence: 96%
“…The possibility of entering in higher education is a constant goal, so expanding vocational training and the entry of qualified professionals at this level of education can contribute to the quality indices of education 16,17 . Milan et al 15 reinforce that the teaching performance valorization makes this a competitive area, bringing to the postgraduate scenario the constant search for best qualification. Nevertheless, the search for short-term experiences encourages graduates to take a course immediately one after the other, and this is clearly a market perspective 15 .…”
Section: Discutionmentioning
confidence: 98%
See 3 more Smart Citations